Implementing a national non-communicable disease policy in sub-Saharan Africa: Experiences of key stakeholders in Ghana - Gertrude Nsorma Nyaaba; Karien Stronks; Lina Masana; Cristina Larrea- Killinger; Charles Agyemang (Elsevier, 2020)
Introduction: Comprehensive national non-communicable disease (NCD) policy development and implementation are crucial for preventing and controlling the increasing NCD burden, particularly in the Africa region where the largest increase in NCD related mortality is expected by 2030. Yet, even where national NCD policies exist, effective implementation remains hindered for reasons not clearly elucidated. This study explored the experiences of key health stakeholders at national and sub-national levels with implementing a national NCD policy in Ghana. Methods: This was an explanatory, cross-sectional and grounded theory study using in-depth interview guides to collect primary data from 39 purposively sampled health policymakers and implementing officials at the national and sub-national levels in Ghana. A thematic approach was used in data analysis. Results: Several interwoven factors including poor policy awareness, poor coordination and intersectoral engagements and inadequate funding for NCD programs and activities are key challenges thwarting the effective implementation of the national NCD policy in Ghana. At the sub-national levels, inadequate clarity and structure for translating policy into action and inadequate integration further affect operationalizing of the national NCD policy. Conclusion: The findings call for policymakers to adopt a series of adaptive measures including sustainable NCD financing mechanisms, effective intersectoral coordination, policy sensitisation and capacity building for implementing health professionals, which should be coupled with governmental and global resource investment in effective implementation of national NCD policies to make sustained population level gains in NCD control in Ghana and in other resource constrained settings.